QoS-aware evaluation criteria for web service composition - Movahednejad, Homa (Asian Research Publishing Network (ARPN), 2014)
Service composition is becoming increasingly pervasive, affecting the way service computing is utilized. Service composition has become an essential element of service deployment due to the fact that single services are unable to fulfill user requirements. Owing to the dramatic growth of services claiming similar functionalities, creating a value-added composite service from a number of candidate services to address the desired goals is a challenging task. To overcome this challenge, various Quality of Service (QoS) aware Web Service Composition (WSC) approaches have been implemented and have a significant impact on composition efficiency. However, there is a lack of knowledge on the impact of such approaches on service composition processes. Hence, this study is aimed to evaluate existing approaches based on QoS aspects. A mathematical-based QoS-aware evaluation framework is proposed and tested on the state-of-the-art approaches. The criteria used for evaluation are first identified from a comprehensive review of related literature. Multi Criteria Decision Making technique is applied in order to formulate a new QoS-aware evaluation method for Web Service Composition approaches based on the identified criteria. The approaches are evaluated using the proposed method to prove its applicability and correctness. The results demonstrate how a service composition approach addresses QoS aspects and assists researchers in outperforming their service composition solutions. The statistical results show the efficiency and correctness of the evaluation method.